Effect of root architecture on tree stability - Zhang, Qiyu (2017)
Tree stability is of paramount significance in heavily vegetated countries like Singapore as any overturning or uprooting of trees could lead to fatality or severe injuries. This study examined the effect of root architecture on tree stability through numerical modelling and physical tests. Due to the destructive nature and high cost associated with experimenting real trees, three-dimensional (3D) printing technology was used to print 3D tree models for physical tests. It is relatively new to utilize 3D printing in geotechnical engineering. Therefore, few research works have been carried out by utilizing 3D printing to study tree stability. However, some research works were carried out on real trees and their results formed the basis for this study (Blackwell et al., 1990; Coutts, 1983; Rahardjo et al., 2009). Numerical analyses were performed using ANSYS software. Both bonded and no separation cases for the root-soil system were considered which showed that missing primary tension root and primary compression root (both in the wind direction), lead to the most vulnerable condition for trees. Physical winching tests were conducted on the 3D printed models and measurements were made using strain gauges and data logger. Both numerical analyses and physical tests showed that tension roots on the windward failed first when tree is subjected to external wind loading. Then failure of compression roots on the leeward side followed. Moreover, results of numerical analyses and physical tests achieved the same order of magnitude of strains which account for the applicability of 3D printing technology in this study. Those two methods also complement each other since physical tests also measured residual strain changes after failure while strain change at any point on the tree before failure can be calculated using ANSYS modelling. Many improvements can be made in future study, such as using more sensitive load cell, printing more tree models of different root architectures, and using multi-material 3D printer, to obtain valuable information.